Association of hair iron levels with creativity and psychological variables related to creativity - Takeuchi, Hikaru; Taki, Yasuyuki; Sekiguchi, Atsushi; Nouchi, Rui; Kotozaki, Yuka; Nakagawa, Seishu; Miyauchi, Carlos M.; Iizuka, Kunio; Yokoyama, Ryoichi; Shinada, Takamitsu; Yamamoto, Yuki; Hanawa, Sugiko; et al. (Frontiers in Human Neuroscience, 2013)
Creativity generally involves the conception of original and valuable ideas. Previous studies have suggested an association between creativity and the dopaminergic system, and that physical activity facilitates creativity. Iron plays a key role in the dopaminergic system and physical activity. Here, we newly investigated the associations between hair iron levels and creativity, dopamine-related traits and states [novelty seeking, extraversion, and vigor (motivational state)], as well as the physical activity level. In the present study, we addressed this issue by performing a hair mineral analysis to determine iron levels and a behavioral creativity test of divergent thinking and related psychological measures among young adults (254 men, 88 women; mean age 20.79 ± 2.03 years). Iron levels did not show any significant association with creativity but displayed significant positive associations with novelty seeking, extraversion, and physical activity level. These results may be partly congruent with the notion that iron plays a key role in the dopaminergic system and imply that iron is important for traits and physical activity, which facilitate creativity. Future interventional or longitudinal studies are warranted to identify any causal effects.